Implementasi Program Keluarga Harapan (PKH) dalam Meningkatkan Kualitas Hidup Masyarakat (Studi Kasus di Kabupaten Probolinggo) - Damayanti, Aldiastri (Jurnal Ilmiah Administrasi Publik, 2016)
This paper examines the real description about the effect of implementationfamily program expectation since 2007 until 2014 in Probolinggo District.Poverty data came from Central Bureau of Statistics (data treated from Indonesian Socio-Economic Survey 2007) also some statistical report. Qualitative approach used for knowing is all the poor receiving the donation. Analysis shows there are not suitable data because referring to old data from Central Bureau of Statistics. Therefore it effects to uneven donation receiver. This paper conclude that donation distribution finding many obstacle caused place for distribution of funds located at capital district, so that difficult to reach it.